THE INFLUENCE OF THE DECISIONS OF THE 41ST IСAO ASSEMBLY ON THE DEVELOPMENT OF CIVIL AVIATION - Chulinda, Liudmyla (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to analyze the decisions of the 41st IСAO Assembly to determine the main trends in the development of civil aviation, their impact on the further development of international civil aviation to ensure international peace and security. Research methods: applied, in particular, comparative and systematic methods to find out the essence and effectiveness of the implementation of the decisions of the IСAO Assembly into the national legal system with the aim of creating a safe international aviation space, which is based, in particular, on identical rules in the field of flight safety, aviation security, organization air traffic, protection of consumer rights, computer reservation systems. Results: it was established that the priority issues approved by the participants of the 41st IСAO Assembly are legally binding for all member states, which should ensure the effectiveness of their implementation for all member states. Proper implementation of the decisions of the IСAO Assembly into national legal systems will increase the safety and efficiency of international civil aviation, will contribute to the support of safe, secure and sustainable development of international air transport. Discussion: the implementation of the decisions of the IСAO Assembly by the member states, in particular, Ukraine, strengthens the integration processes, as it establishes mandatory rules, technical requirements, administrative procedures and basic operational standards, the decisions of the IСAO Assembly need to be properly studied and implemented into the national legislation of the member states. The characteristics of the decisions of the 41st ISAO Assembly allow us to conclude that they direct the activities of international and European civil aviation organizations, which is important for all mankind, since civil aviation is one of the most important branches of the national economy, the effective functioning of which is a necessary condition for the stabilization and development of international activities, meeting the needs of the population in air transportation, ensuring the protection of the national interests of Ukraine.